2006
DOI: 10.1111/j.1464-5491.2005.01779.x
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes—prevalence and cost of illness in Germany: a study evaluating data from the statutory health insurance in Germany

Abstract: In accordance with the results of recent studies using routinely collected health insurance data, our study suggests that the prevalence of diabetes mellitus has increased steadily in the past years. The prevalence in our population of 14.7 million insured was 6.45%. Total costs of diabetes mellitus amounted to Euro 5.71bn.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
39
1
4

Year Published

2006
2006
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 24 publications
6
39
1
4
Order By: Relevance
“…Even though the concept of the human capital method in economic appraisal is somewhat controversial (van Roijen et al, 1995), our approach to calculate indirect costs is in line with former studies on similar topics (Stock et al, 2006). For the calculation of direct costs of LB hospital care, the number of annual cases for adults and adolescents was multiplied by their annual median cost per hospital stay.…”
Section: Discussionmentioning
confidence: 99%
“…Even though the concept of the human capital method in economic appraisal is somewhat controversial (van Roijen et al, 1995), our approach to calculate indirect costs is in line with former studies on similar topics (Stock et al, 2006). For the calculation of direct costs of LB hospital care, the number of annual cases for adults and adolescents was multiplied by their annual median cost per hospital stay.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of hypertension in 6 European countries is 44.2%, ranging from 55% in Germany to 38% in Italy [26]. With regard to diabetes, its prevalence has been increasing in all Western countries, although the prevalence has been greater in the US [27] than in most European countries [28] (9.3 vs. 3.5–6.5%). Surprisingly, PREVADIAB showed that the standardized prevalence estimates of diabetes in Portugal (11.7%) are similar to those in the US, and greater than previously estimated by the WHO.…”
Section: Discussionmentioning
confidence: 99%
“…There are only a few other studies on medication costs among diabetic patients in Germany (11)(12)(13). A comparison of these studies is difficult because of different study designs and populations.…”
Section: Prescription Prevalences and Costsmentioning
confidence: 99%